Collaboration and Communication Skills in Problem-Based Learning in Basic Tax Competencies - Tiara Tiara; Annisa Istiqlallia; Sri Kantun (Jurnal Pendidikan Ekonomi, 2024)
Collaboration and communication skills are needed for students during economics learning. Therefore, this study aims to analyze collaboration and communication skills in problem-based learning in the basic competencies of taxation. The research method used quantitative descriptive research to deal with the research purposes. The results of this research showed that the overall average indicator of students’ collaboration skills was in sufficient category, and the overall average indicator of students’ communication skills was in the high category. In addition, students’ response to learning economics using problem-based learning is good. Almost all students can understand the material in the teaching and learning activities in the basic tax competencies, especially within groups. The recommendation in this study is that teachers need to improve their ability to form creative and innovative learning in problem-based learning. Another recommendation when designing the learning, the suitable learning model is needed to encourage student collaboration and communication.